Letters from a Father to his Daughter (Gurugram Penguin, 2004)
The collection of these letters spans over a large range and has many topics covered in it. Nehru began writing to his 10-year-old daughter when she was in Mussourie and he was in Allahabad. In order to tell his daughter about all the wonderful things in the world and his many thoughts on people and the society, he wrote her diverse letters that initially spoke of how the earth was formed, how animal and human life came into existence and how societies entered the fray. Nehru further also writes about races, faith and beliefs that existed in those times. The letters cover a major portion of human history and the history of India as well.
Keywords: Indian Freedom Struggle-Jawaharlal Nehru